Setting agenda abroad: exploring the agenda-setting potential of homeland online newspapers on perceptions of elections issues among diasporic Nigerians in Malaysia - Mustapha, Lambe Kayode; Wok, Saodah (2013)
The increasing transnational migration of people and availability of homeland newspapers on the web have stimulated interest in the understanding of the use and effects of homeland media on nations’ foreign residents. This study explored the relationship between agenda of issues covered in Nigerian online newspapers and the agenda of issues perceived by Nigerian students in Malaysia during the 2011 Nigerian presidential election. Specifically, the overall issues agenda in the online newspapers, agenda of issues in news story location (homepage and index), and agenda of issues in news story length (long and short) were compared with the agenda of important issues perceived by Nigerian students in Malaysia. With hypotheses that are rooted in salience correspondence envisaged by the agenda setting research, the study combined data from a content analysis of three Nigerian online newspapers and a survey of Nigerian students in Malaysian institutions of higher learning. Findings revealed a modest but plausible support for the agenda-setting potential of the online newspapers and suggested the need to explore other cues in the online newspapers that are capable of raising the salience of issues in the diasporic public perceptions.